EXPERIENCE OF SIMULATION-BASED TRAINING OF ANESTHESIOLOGISTS AND EMERGENCY PHYSICIANS - I. D. Rаykin; M. I. Neymаrk; V. V. Shmelev; S. A. Khаustovа; A. Yu. Elizаriev (Вестник анестезиологии и реаниматологии)
The article describes the topicality of simulation-based technologies as a part of the practical training of anesthesiologists and emergency physicians. It validates the theoretical and practical background for inclusion of simulation-based technologies into the training in order to decrease the number of medical errors in one of the most highly technical fields of modern medicine. The authors share the experience of staged simulation-based training of anesthesiologists and emergency physicians in the Simulation Center of Altai State Medical University by the Russian Ministry of Health.